Kinetic and thermodynamic parameters guiding the localization of regioselectively modified kaolin platelets into a PS/PA6 co-continuous blend. (16th March 2020) - Taguet, Aurélie; Otazaghine, Belkacem; Batistella, Marcos
Abstract: This article highlights the role of kinetic and thermodynamic parameters on the localization of modified kaolin platelets into a high interfacial tension co-continuous PS/PA6 blend after extrusion, injection molding and annealing. Three kinds of copolymers were synthesized and grafted on kaolin: poly(styrene-co-(methacryloyloxy)methyl phosphonic acid) copolymer (P(S-co-MAPC1 (OH)2 )), polystyrene terminated 3-(mercaptopropyl)triethoxysilane, (ETS-PS) and poly(styrene-co-3-methacryloxypropyltrimethoxysilane) copolymer, (P(S-co-MPS)). Those copolymers were distinguished by (1) the nature of their functional groups (phosphonic acid that reacts only with aluminol groups or alkoxysilane that reacts with both silanol and aluminol groups), (2) the amount of functional groups and (3) their molecular weights. After functionalization the kaolin samples (K1, K2 and K3, respectively) were analyzed by FTIR, TGA and Py-GC/MS to evaluate the grafting. It was shown that P(S-co-MAPC1 (OH)2 ) and P(S-co-MPS) copolymers grafted on kaolin led to highly anisotropic K1 and K3 kaolin platelets, respectively. Then, 50/50/5 PS/PA6/Ki samples (i = 0 to 3) were processed as follows: (1) kaolin platelets were dispersed (via solvent cast) into the PS phase. Then, (2) PS + kaolin were melt mixed by microcompounder with PA6, then (3) the PS/PA6/Ki were injection molded into disks and finally (4) they were annealed (via dynamic or quiescent annealing). Thanks to the high shear rate and longtime of mixing during extrusion (microcompounder), all the kaolin platelets (unmodified K, K1, K2 and K3) crossed the interface and were localized in the PA6 phase. All Ki kaolin stayed in the PA6 phase during injection. However, after annealing (quiescent or dynamic), the localization of the nanoplatelets was guided by thermodynamic parameters, and SEM analysis revealed the segregation of K1 and K3 kaolin platelets at the polymers interface, with a high tendency to impede polymer phases coalescence. Hence, modified K1 and K3 kaolin are promising compatibilizing agents for a co-continuous PS/PA6 blend. Graphical abstract: Image 1 Highlights: Copolymers bearing either phosphonic acid or silanol reactive functions are synthesized and grafted on kaolin platelets. The three kinds of functionalized kaolin (K1, K2 and K3) are incorporated into a co-continuous PS/PA6 blend. K, K1, K2 and K3 are localized in the PA6 phase after extrusion and injection. K1 and K3 functionalized kaolin are localized at the interface after quiescent or dynamic annealings.